Are 'the affluent' responsible for global poverty?. Issue 1 (1st January 2019) - Lawford-Smith, Holly
ABSTRACT: According to Christian Barry & Gerhard Øverland (2016), there are multiple ways "the affluent" might be morally responsible for the situation the global poor are in, including having failed to assist them on a single occasion or on multiple occasions; by enabling harm to them; by 'giving rise to cost' for them; by making it costly for the poor to escape their own suffering; by exploiting them; by overdetermining harm to them. But what exactly is this group, "the affluent", who Barry and Øverland present as being capable of doing all these things? In this paper I present three possible conceptions of 'the affluent', and argue that they all create problems for the conclusions the authors want to reach.